1997
DOI: 10.1074/jbc.272.17.11350
|View full text |Cite
|
Sign up to set email alerts
|

A Common Binding Site Mediates Heterodimerization and Homodimerization of Bcl-2 Family Members

Abstract: Bcl-2 inhibits apoptosis induced by a wide variety of stimuli. In contrast, the Bcl-2 homologue, Bax, antagonizes Bcl-2's death protecting function. Bcl-2 forms protein-protein homodimers with itself and heterodimers with Bax, and previous experiments have shown that point mutations in Bcl-2 can abrogate Bax binding while leaving homodimerization intact. These mutagenesis results can be interpreted to suggest that Bcl-2 has separate binding sites that are responsible for homodimer and heterodimer formation. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 26 publications
8
93
0
Order By: Relevance
“…The structure of a BAK BH3 peptide in complex with BCL-X L revealed that the hydrophobic groove was indeed the contact site for proapoptotic binding 53 ( Figure 4b). Thus, the protein interaction that accounts for BCL-2 family member homo-and heteroassociations, 50,54,56 and believed to regulate pore formation, was explicitly Figure 4 The structures of antiapoptotic BCL-2 family members (a) and their BH3 peptide complexes (b) revealed a multidomain hydrophobic groove that serves as the critical binding interface for a-helical BH3 domains. Hydrophobic residues are indicated in green and BH3-binding grooves bracketed in black.…”
Section: Bcl-2 Family Form and Functionmentioning
confidence: 99%
“…The structure of a BAK BH3 peptide in complex with BCL-X L revealed that the hydrophobic groove was indeed the contact site for proapoptotic binding 53 ( Figure 4b). Thus, the protein interaction that accounts for BCL-2 family member homo-and heteroassociations, 50,54,56 and believed to regulate pore formation, was explicitly Figure 4 The structures of antiapoptotic BCL-2 family members (a) and their BH3 peptide complexes (b) revealed a multidomain hydrophobic groove that serves as the critical binding interface for a-helical BH3 domains. Hydrophobic residues are indicated in green and BH3-binding grooves bracketed in black.…”
Section: Bcl-2 Family Form and Functionmentioning
confidence: 99%
“…This interaction is governed by both hydrophobic and electrostatic forces, and disruption of either by introduction of alanine at several sites along the Bak peptide's length was sufficient to abolish binding. BH3 peptides also disrupt dimerization among other members of the family, including Bcl-2 and Bax (Diaz et al, 1997) A bacterial connection?…”
Section: Bcl-x L Structure and Implications For Functionmentioning
confidence: 99%
“…Regulation of outer mitochondrial membrane permeabilization is the major way in which Bcl-xL protein exerts its anti-apoptosis regulatory and survival effect, which means preserving mitochondrial membrane integrity, mitochondrial transmembrane potential as well as ATP production, and preventing the release of apoptogenic factors in cytosol (reviewed in [2][3][4]). Elucidation of Bcl-xL's 3-dimensional structure has provided a first structural model in which α-helices located in BH1 (Bcl-2 homology domain), BH2 and BH3 domains create an elongated hydrophobic pocket domain where a BH3 amphipathic α-helice of another Bcl-2-like protein can bind [5][6][7]. Bcl-xL binds to pro-apoptotic family members through proteinprotein interactions, forming a complex dynamic network of hetero-oligomers, depending on the cellular environment, stress condition and their subcellular localization [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%